Study on the removal of fine particles by using water in a rotating packed bed. (19th January 2017) - Li, Ze‐Yan; Dong, Kun; Liang, Yan; Zhang, Lili; Sun, Baochang; Chu, Guang‐Wen; Zou, Hai‐Kui; Chen, Jian‐Feng
Abstract: This study presented an experimental investigation on the capture of fine particles from gas stream by water in a rotating packed bed (RPB). Experiments were carried out to investigate the effects of different operating conditions including packing types, rotation speed, gas‐liquid volumetric ratio, inlet particle concentration, and gas temperature on the removal efficiency of fine particles. The overall removal efficiency of fine particles can reach 98 % under the optimal operating conditions, which are a rotation speed of 1200 rpm, a gas‐liquid volumetric ratio of 600, a gas temperature of 100 °C, and the use of fine metal gauze packing. In addition, the correlation of removal efficiency of fine particles was deduced. It is observed that the predicted removal efficiency and outlet concentration of fine particles are in good agreement with the experimental values, with deviations within 10 % and 20 % respectively. This process exhibits the potential application of RPBs in simultaneous removal of fine particles and SO2 by liquid solution. Abstract : The graphical abstract presents the removal of fine particles by using water in a rotating packed bed. Here the gray circle indicates dusty gas; the middle device is the rotating packed bed (RPB). When the dusty gas containing fine particles goes through the RPB, fine particles can be captured by the RPB efficiently. Also, the correlation equation agrees well with experimental data.